(untitled) (Herald of the National Children’s Medical Center, 2025)
The probability of developing Low Cardiac Output Syndrome (LCOS) after radical correction of Transposition of the Great Arteries (TGA) in newborns is high. Effective hemodynamic management is crucial, as delays or inadequate intervention can lead to irreversible organ damage. The choice of appropriate inotropic support plays a vital role in patient survival, requiring timely and well-informed decisions by the cardiac intensivist, whose expertise is critical in optimizing postoperative outcomes.